Sarcopenia da caquexia reumatoide: conceituação, mecanismos, consequências clínicas e tratamentos possíveis - Rocha, Oswaldo Melo da [UNESP]; Batista, Andréa de Almeida Peduti [UNESP]; Maestá, Nailza [UNESP]; Burini, Roberto Carlos [UNESP]; Laurindo, Iêda Maria Magalhães (Elsevier Editora Ltda, 2009)
A caquexia relacionada à artrite reumatoide é conceituada como perda involuntária de massa magra, predominantemente de músculo esquelético, que também ocorre em vísceras e sistema imune, com massa gorda estável ou um pouco elevada e com pequena ou nenhuma perda de peso. A causa é multifatorial, incluindo a produção acentuada de citocinas, principalmente TNF± e IL-1², diminuição da ação periférica da insulina e pouca atividade física. A caquexia se faz presente em doentes com AR ativa ou mesmo inativa. Neste artigo discutem-se aspectos relacionados à patogenia, implicações clínicas e possíveis opções terapêuticas.

Rheumatoid cachexia can be defined as an involuntary loss of body cell mass, which predominates in skeletal muscle, but is also observed in the viscera and immune system. It occurs with little or no weight loss in the presence of stable or increased fat mass. The etiology is likely multifactorial, and involves excessive inflammatory cytokine production, namely excess tumor necrosis factor-± and interleukin-1² production, reduced peripheral insulin action, and low habitual physical activity. Cachexia occurs in active rheumatoid arthritis and even in the presence of disease control. In this article, we discuss the pathogenesis of rheumatoid cachexia, its clinical implications and potential therapies.
Sarcopenia in rheumatoid cachexia: definition, mechanisms, clinical consequences and potential therapies
Keywords: sarcopenia; caquexia; artrite reumatoide; composição corporal; body composition; cachexia; rheumatoid arthritis; sarcopenia